Information processing among high-performance managers - S.C. Garcia-Santos; L.S. Almeida; B.S.G. Werlang; A.L.M. Veloso (Desafio Singular, 2010)
The purpose of this study was to evaluate the information processing of 43 business managers with a professional superior performance. The theoretical framework considers three models: the Theory of Managerial Roles of Henry Mintzberg, the Theory of Information Processing, and Process Model Response to Rorschach by John Exner. The participants have been evaluated by Rorschach method. The results show that these managers are able to collect data, evaluate them and establish rankings properly. At same time, they are capable of being objective and accurate in the problems assessment. This information processing style permits an interpretation of the world around on basis of a very personal and characteristic processing way or cognitive style.